2023
DOI: 10.1371/journal.pdig.0000173
|View full text |Cite
|
Sign up to set email alerts
|

A novel smartphone application for the informal caregivers of cancer patients: Usability study

Abstract: Informal caregivers are a critical source of support for cancer patients. However, their perspectives are not routinely collected, despite health impacts related to the burden of caregiving. We created the TOGETHERCare smartphone application (app) to collect observer-reported outcomes regarding the cancer patient’s health and caregiver’s perceptions of their own mental and physical health, and to provide tips and resources for self-care and patient care. We enrolled 54 caregivers between October 2020 and March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…There is little research against which to compare the level of adequate/inadequate health literacy in this sample. Although similar to a study of informal caregivers (Oakley-Girvan et al, 2023), a previous study carried out with cancer caregivers found a much higher proportion of cancer caregivers had limited health literacy compared to the current sample (Gabriel et al, 2021). This contrast may be explained by that study being conducted in a developing country with limited cancer services which may explain the poor health literacy among cancer caregivers (Gabriel et al, 2021).…”
Section: Discussionsupporting
confidence: 70%
“…There is little research against which to compare the level of adequate/inadequate health literacy in this sample. Although similar to a study of informal caregivers (Oakley-Girvan et al, 2023), a previous study carried out with cancer caregivers found a much higher proportion of cancer caregivers had limited health literacy compared to the current sample (Gabriel et al, 2021). This contrast may be explained by that study being conducted in a developing country with limited cancer services which may explain the poor health literacy among cancer caregivers (Gabriel et al, 2021).…”
Section: Discussionsupporting
confidence: 70%
“…An increasing significance to the assimilation of telepsychiatry into health systems is driven by the emergence of multiple mobile applications that provide additional data concerning patients’ health and generating tighter communication between the different caretakers, and even informal caregivers . 42 Thus, apps that are unique to telepsychiatry could facilitate multiple advancements such as joint meetings of a group of caretakers exchanging ideas and data, 43 , 44 streaming of data collected from mobile-based apps that provide data concerning voice modulation, movement, money spending, social interactions, frequency of phone calls, and other data, 45 48 and also enable psychotherapeutic groups sessions 49 , 50 omitting the logistical requirements within a clinical facility.…”
Section: Discussionmentioning
confidence: 99%
“…The studied PRO-CTCAE symptoms were chosen by the study team of KPNC oncologists (RL and EN) based on the known or anticipated effects of the therapies in the study patient population. The following symptoms were selected for inclusion in the apps: nausea, anxiety, pain, sadness, vomiting, appetite, constipation, diarrhea, shortness of breath, numbness, insomnia, and fatigue [18]. We created a total count of each severe or very severe symptom reported by the participant on the PRO-CTCAE.…”
Section: Symptom Reportingmentioning
confidence: 99%